Somatic embryogenesis as an alternative for in vitro multiplication of Butia odorata from mature zygotic embryos - CAMPOS,SAMANTA S. DE (2020)
Abstract Butia odorata is a palm native to southern Brazil and Uruguay, not domesticated, much appreciated for its fruits and economic potential. However, the extractivism and the difficulty of propagation have led to the decline of natural populations. The objective of this work was to prove the possibility of induction of somatic embryogenesis in B. odorata. Mature zygotic embryos were induced in two media, MS and Y3, combined with auxin 2,4-D and picloram in five concentrations (2,4-D: 0, 361.99, 452.49, 542.99 and 633.48 μM/L, picloram: 0, 50, 150, 300 and 450 μM/L). The results promising during induction with the formation of embryogenic calli and somatic embryos, however the regeneration of them was not efficient, this may be due to the occurrence of somatic embryos fused during its development. The roots were formed, but the aerial part remained molten, not completing its development. Auxin picloram and Y3 medium provided the most adequate conditions for calogenesis, formation of embryogenic callus and somatic embryos, with concentrations of 150, 300 and 450 μM/L. This is the first description of somatic embryogenesis in B. odorata that will serve as the basis for future research and adjustments of the methodology proposed here.